METHODS, WAYS AND TECHNOLOGIES OF ORGANIZING MODERN FOREIGN LANGUAGE LEARNING - Ma’murova Navruzakhon Sherzodbek qizi; Ahmedova Matlubaxon Ibragimjonovna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation: The field of modern foreign language learning has seen significant advancements in methods, ways, and technologies that have transformed the way languages are taught and learned. In this article, we will explore some of the key approaches and tools that are shaping language education today.Organizing modern foreign language learning involves a diverse set of methods, approaches, and technologies aimed at creating engaging, effective, and inclusive learning experiences. Let's delve into a variety of these techniques.